Tobacco use health implications and cessation intervention - San Juan, Sofronio P. (The Journal of the Philippine Dental Association)
Tobacco is a great global problem affecting all segments of the population. It is definitely a hazard to health. Death resulting from tobacco use presents many faces like, cancer, heart disease, oral diseases, toxic poisoning and disabilities. Unfortunately, it still remains unrecognized as a public health risk in many countries, particularly in developing ones, including the Philippines. Cessation activities are still at very low-intensity and do not have very high success rates. This may be due to lack of public information and wider dissemination of anti-tobacco issues... not to mention the lack of political will on the part of the government to enforce existing legislation towards this end.